Royal sculpture in Egypt 300 BC - AD 220 - Brophy, EM (2014)
The aim of this thesis is to approach Ptolemaic and Imperial royal sculpture in Egypt dating between 300 BC and AD 220 (the reigns of Ptolemy I and Caracalla) from a contextual point of view. To collect together the statuary items (recognised as statues, statue heads and fragments, and inscribed bases and plinths) that are identifiably royal and have a secure archaeological context, that is a secure find spot or a recoverable provenance, within Egypt. I then used this material, alongside other types of evidence such as textual sources and numismatic material, to consider the distribution, style, placement, and functions of the royal statues, and to answer the primary questions of where were these statues located? what was the relationship between statue, especially statue style, and placement? And what changes can be identified between Ptolemaic and Imperial royal sculpture? From analysis of the sculptural evidence, this thesis was able to create a catalogue of 103 entries composed of 157 statuary items, and use this to identify the different styles of royal statues that existed in Ptolemaic and Imperial Egypt and the primary spaces for the placement of such imagery, namely religious and urban space. The results of this thesis, based on the available evidence, was the identification of a division between sculptural style and context regarding the royal statues, with Egyptian-style material being placed in Egyptian contexts, Greek-style material in Greek, and Imperial-style statues associated with classical contexts. The functions of the statues appear to have also typically been closely related to statue style and placement. Many of the statues were often directly associated with their location, meaning they were an intrinsic part of the function and appearance of the context they occupied, as well as acting as representations of the monarchs. Primarily, the royal statues acted as a way to establish and maintain communication between different groups in Egypt.